In vivo detection of nerve injury in familial amyloid polyneuropathy by magnetic resonance neurography - Hayes, Jennifer; Hund, Ernst; Hornung, Benjamin; Hegenbart, Ute; Schönland, Stefan; Kimmich, Christoph; Kristen, Arnt; Purrucker, Jan; Röcken, Christoph; Heiland, Sabine; Bendszus, Martin; Pham, Mirko (Brain, 2015)
Transthyretin familial amyloid polyneuropathy is a rare, autosomal-dominant inherited multisystem disorder usually manifesting with a rapidly progressive, axonal, distally-symmetric polyneuropathy. The detection of nerve injury by nerve conduction studies is limited, due to preferential involvement of small-fibres in early stages. We investigated whether lower limb nerve-injury can be detected, localized and quantified in vivo by high-resolution magnetic resonance neurography.